2009
DOI: 10.1007/s10750-009-9848-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiple in-to-Africa dispersals of labeonin fishes (Teleostei: Cyprinidae) revealed by molecular phylogenetic analysis

Abstract: An out-of-Africa dispersal route has been proposed for many organisms, including modern man. However, counter examples of in-to-Africa dispersal routes are less common. In the present article, the phylogenetic relationships within the Labeoninae, a subfamily of cyprinid fishes distributed in Asia and Africa, were analyzed to investigate the biogeographic processes governing the modern distribution of these Asian and African cyprinids. The mitochondrial DNA cytochrome b gene was used as a molecular marker. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
3
21
1
Order By: Relevance
“…The resolution of Discogobio and Ptychidio in the subfamily Cyprininae is consistent with Chu (1935) and Bȃnȃrescu and Nalbant (1965), as well as more recent studies (e.g. Kong et al, 2007;Wang et al, 2007;Li et al, 2008;Tang et al, 2009;Yang and Mayden, 2010;Zheng et al, 2010). Although Luciocyprinus was not examined, its treatment in the literature (e.g.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The resolution of Discogobio and Ptychidio in the subfamily Cyprininae is consistent with Chu (1935) and Bȃnȃrescu and Nalbant (1965), as well as more recent studies (e.g. Kong et al, 2007;Wang et al, 2007;Li et al, 2008;Tang et al, 2009;Yang and Mayden, 2010;Zheng et al, 2010). Although Luciocyprinus was not examined, its treatment in the literature (e.g.…”
Section: Discussionsupporting
confidence: 83%
“…Bȃnȃrescu and Nalbant disagreed with Lin (1933) on the placement of Ptychidio and Discogobio, removing both genera from Gobioninae to Cyprininae, hypothesizing that they are closely related to Garra. This affiliation with Garra and/ or other labeonins within the subfamily Cyprininae has been corroborated by several recent molecular studies (Kong et al, 2007;Wang et al, 2007;Li et al, 2008;Tang et al, 2009;Yang and Mayden, 2010;Zheng et al, 2010). Bȃnȃrescu and Nalbant reported the presence of an encapsulated air bladder in Microphysogobio, a genus not examined by Ramaswami (1955), which they thought was more closely related to Pseudogobio and Abbottina, genera with free swim bladders, than Saurogobio, a genus with an encapsulated swim bladder.…”
Section: Taxonomic Historymentioning
confidence: 52%
“…The labeonine fishes dispersed into Africa twice within the Labeoninae, one within the species of Labeo, and the other within the species of Garra. This result is consistent with the view of two dispersal events of labeonins from Asia into Africa in Tang et al (2009). Labeoninae dispersed into East Asia (China) and South Asia several times from Southeast Asia, and a few East Asian species dispersed back into Southeast Asia.…”
Section: Fig 4 Ancestral Distribution Ranges Inferred By S-diva Analsupporting
confidence: 92%
“…Tang et al (2009) suggested that the origin centre of the Labeoninae was East Asia and two dispersal events of labeonines from Asia into Africa. Yang and Mayden (2010) also supported this dispersal opinion.…”
mentioning
confidence: 99%
“…The monophyly of the tribe Labeonini has been confirmed by previous morphological (Reid, 1982(Reid, , 1985Chen et al, 1984;Cavender and Coburn, 1992;Stiassny and Getahun, 2007) and molecular studies (Li et al, , 2008Rüber et al, 2007;Wang et al, 2007;Tang et al, 2009;Zheng et al, 2010). Historically, the tribe Labeonini has been subdivided into two (Rainboth, 1991(Rainboth, , 1996Stiassny and Getahun, 2007), three (Zhang et al, 2000;Zhang and Chen, 2004), or five (Reid, 1982(Reid, , 1985 groups.…”
Section: Introductionmentioning
confidence: 75%